2019
DOI: 10.1093/esr/jcz063
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Motherhood Penalty in Academia? The Gendered Effect of Children on Academic Publications in German Sociology

Abstract: Based on data that tracks curriculum vitae (CV) and publication records as well as survey information from sociologists in German academia, we examine the effects of parenthood on the publication output of male and female academics that were present in German universities or research institutes in the year 2013. Results indicate that having children leads to a significant decline in the number of publications by women on average, while not affecting the number of publications by men. However, the gendered effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 45 publications
2
47
0
2
Order By: Relevance
“…To sum up, ours is the first study to use a virtually complete sample of all German academic political scientists to show that women tend to be favored over men in the hiring process for tenured professorships, before and after controlling for various factors, most importantly productivity (but see [ 65 , 66 ] for the discipline of sociology in Germany). This means that women get hired with fewer measurable publications than men do, indicating that there is no bias against women when judging their competency, different from what other studies found [ 20 : 342, 44 : 3].…”
Section: Discussionmentioning
confidence: 99%
“…To sum up, ours is the first study to use a virtually complete sample of all German academic political scientists to show that women tend to be favored over men in the hiring process for tenured professorships, before and after controlling for various factors, most importantly productivity (but see [ 65 , 66 ] for the discipline of sociology in Germany). This means that women get hired with fewer measurable publications than men do, indicating that there is no bias against women when judging their competency, different from what other studies found [ 20 : 342, 44 : 3].…”
Section: Discussionmentioning
confidence: 99%
“…Gender-neutral policies extend equal benefits to new mothers and fathers, whereas female-only policies are only available to women. 8 Both types of policies typically stop the tenure clock for one year for each new child, up to a maximum of two. Table 1 reports gender-neutral and female-only policy adoption dates for the universities in our sample.…”
Section: Tenure Clock Stopping Policiesmentioning
confidence: 99%
“…Finkel, Olswang, and She (1994) find a large share of female faculty believe that using family friendly policies will hurt their career. 8 What we call female-only policies are sometimes instead called primary caregiver policies, and cover parents of either gender who provide more than 51 percent of caregiving activities. Gender-neutral policies sometimes require parents to have "significant" childcare responsibilities, but can be used simultaneously by both parents.…”
Section: Tenure Clock Stopping Policiesmentioning
confidence: 99%
“…Another body of research suggests that having children does have a negative effect on female research performance in comparison with male performance (see, e.g. Fox 1995;Fuchs, von Stebut, and Allmendinger 2001;Hunter and Leahey 2010;Ecklund and Lincoln 2011;Lutter and Schröder 2019). The results of Ginther and Kahn (2006) provide a more complex picture, suggesting that there are field-specific differences in the effect of having children and that the effect is very low in most research fields.…”
Section: Explanations Of the Productivity Puzzlementioning
confidence: 99%